Factors affecting school performance in children with rheumatic heart disease - Arief Hermanu S.; Sudigdo Sastroasmoro; Bambang Madiyono; Ismet N. Oesman (Paediatrica Indonesiana, 2001)
The aim of this study was to determine the association between school performance and age, sex, duration of illness, educational achievement prior to illness, socioeconomic status of family, parentâ€™s educational level, number of children in the family and severity of the disease of patients with rheumatic heart disease (RHD). Subjects were patients with RHD treated at the Division of Cardiology, Department of Child Health, Cipto Mangunkusumo Hospital Jakarta. The parameters of school performance were educational achievement, absent of school and dropout. All data were processed by using Epi-Info program to find out bivariate analysis and Statistic Program for Social Sciences (SPSS) for multivariate analysis. We obtained 80 patients with RHD; most of them were of mild severity (64 of 80%) and the remainder 16 (20%) with severe disease. There were 44 (55%) males and 36 (45%) females. Most parents (42 or 53%) had junior high school educational level, most of them, 23 (29%) had elementary school education, and 3 (4%) illiterate. Bivariate and multivariate analyses showed that severity of disease and parental educational level were associated withschool performance of patients with RHD, but age, sex, duration of disease, premorbid educational achievement, socio-economic level of the family and number of children in family were not. Â